Computational Treatment for the Coupled System of Viscous Burger’s Equations through Non-central Formula in the Method of Lines (European Journal of Pure and Applied Mathematics, 2024)
Viscous Burger’s equation is one of the most celebrated models with immense applications cutting across all aspects of mathematical physics. Thus, the present communication makes use of the non-central formula infused in the method of lines coupled with Runge-Kutta spatial discretization to computationally and efficiently treat the coupled system of viscous Burger’s equations. Further, we numerically tested the derived schemes of the governing model amidst suitable initial and boundary data. In fact, we eventually analyzed the effectiveness of the method via L2 and L∞ norms on some test problems and found it to be robust; indeed, a comparison of the current scheme with some notable approaches in the literature has been established, which are realized to be in perfect agreement.
Keywords: method of lines; Nonlinear coupled system; viscous Burger’s equations.